Hypoosmotic and glutamate‐induced swelling of bipolar cells in the rat retina: comparison with swelling of Müller glial cells. (29th May 2013) - Vogler, Stefanie; Grosche, Antje; Pannicke, Thomas; Ulbricht, Elke; Wiedemann, Peter; Reichenbach, Andreas; Bringmann, Andreas
Abstract: Regulation of cellular volume is of great importance to avoid changes in neuronal excitability resulting from a decrease in the extracellular space volume. We compared the volume regulation of retinal glial (Müller) and neuronal (bipolar) cells under hypoosmotic and glutamate‐stimulated conditions. Freshly isolated slices of the rat retina were superfused with a hypoosmotic solution (60% osmolarity; 4 min) or with a glutamate (1 mM)‐containing isoosmotic solution (15 min), and the size changes of Müller and bipolar cell somata were recorded. Bipolar cell somata, but not Müller cell somata, swelled under hypoosmotic conditions and in the presence of glutamate. The hypoosmotic swelling of bipolar cell somata might be mediated by sodium flux into the cells, because it was not observed under extracellular sodium‐free conditions, and was induced by activation of metabotropic glutamate receptors and sodium‐dependent glutamate transporters. The glutamate‐induced swelling of bipolar cell somata was mediated by sodium chloride flux into the cells induced by activation of NMDA‐ and non‐NMDA glutamate receptors, glutamate transporters, and voltage‐gated sodium channels. The glutamate‐induced swelling of bipolar cell somata was abrogated by adenosine and γ‐aminobutyric acid, but not by vascular endothelial growth factor and ATP. The data may suggest that Müller cells, in contrast to bipolar cells, possess endogenous mechanisms which tightly regulate the cellular volume in response to hypoosmolarity and prolonged glutamate exposure. Inhibitory retinal transmission may regulate the volume of bipolar cells, likely by inhibition of the excitatory action of glutamate. Abstract : In the rat retina, bipolar cells display cellular swelling under hypoosmotic conditions and during exposure of glutamate; the swelling is mediated by activation of glutamate receptors and transporters. In contrast, Müller glial cells do not swell under these conditions; this may be of great importance to avoid changes in neuronal excitability resulting from a decrease in the extracellular space volume.